An analysis of sexual dysfunction symptoms in hormone receptor positive breast cancer patients during adjuvant endocrine therapy in a Brazilian center - Pereira, Daniela Jessica; Paes, Flavia Rocha; Paula, Stany Rodrigues de; Suzuki, Daniele Assad; Santos, Danielle Laperche dos; Sousa, Romualdo Barroso; Ferrari, Bruno Lemos; Rodrigues, Angelica Nogueira (Mastology, 2026)
Objective: This study, conducted at a single center in Brazil, aimed to evaluate the impact of endocrine therapy on the sexual lives of 105 patients diagnosed with early-stage breast cancer. Methods: The women selected for this study were diagnosed with early-stage hormone receptor-positive and human epidermal growth factor receptor-type 2-negative (HR+/ HER2-) breast cancer and had been undergoing adjuvant hormone therapy for at least six months. Participants were divided into two groups: those who had engaged in sexual activity in the past four months (considered sexually active) and those who had not (considered sexually inactive). Women in the first group completed the Female Sexual Function Index (FSFI) questionnaire, and sexual dysfunction was identified as a score of ≤26.55. Data were collected using the REDCap software and analyzed using RStudio. Results: A total of 105 women diagnosed with early-stage breast cancer were evaluated. Prior to their diagnosis, 65.4% were sexually active, but only 42.3% reported being sexually active in the four weeks leading up to the questionnaire. The FSFI score indicated sexual dysfunction in 77.3% of patients, with the main contributing factors being low libido and pain during sexual activity, along with other contributing elements. Additionally, patients reported moderate satisfaction with their sexual lives in general. Conclusion: Data analysis revealed a notable decline in the sexual quality of life of patients undergoing hormone therapy. This decline reflects not only the effects of hormone therapy but also the impact of cancer diagnosis and other phases of treatment. The findings highlight the importance of oncologists addressing this issue during consultations and directing patients to seek help, if needed, from specialists in sexology.